Students' Mental Load Viewed from Self-Compassion - Ayuningrum, Diah; Naini, Rohmatus; Muarifah, Alif; Nugraha, Ariadi (International Journal of Applied Guidance and Counseling, 2026)
This study aims to examine the role of self-compassion in mental load among high school students. The study employed a quantitative correlational design and involved 262 students from three high schools in Yogyakarta. Data were collected using the Mental Load Scale and the Self-Compassion Scale. Based on the results of this study, both instruments showed adequate validity and reliability as indicated by AVE, Cronbach’s Alpha, and Composite Reliability values. Analysis was conducted using Partial Least Squares (PLS) based Structural Equation Modeling with SmartPLS 4.0. The validity results showed that all aspects had an Average Variance Extracted (AVE) > 0.50, while internal reliability for all aspects was good with Cronbach’s Alpha and Composite Reliability >0.70. The results showed that total self-compassion had a significant role in total mental load (β = 0.133, p < 0.05) and mental load aspects (β = 0.025, p < 0.05). However, total self-compassion also played an indirect role in mental effort aspects through total mental load as a mediator (T-statistic > 1.96, p < 0.05). The R-square values indicate strong predictive ability in most aspects, including the mental load aspect (0.942) and the mental effort aspect (0.936). These findings indicate that students with higher levels of self-compassion tend to cope more adaptively with academic and emotional pressures. Therefore, school-based guidance and counseling services can be utilized to help students manage mental load by strengthening self-compassion through individual or group counseling.